Offline Educational Games and Learning Motivation Effects on Fourth Grade Social Studies Achievement: An Experimental Study - Salmawati Salmawati; Weni Yulastri; Alfroki Martha (Journal of Education Research, 2026)
Quality education in elementary schools depends significantly on students' learning motivation and the instructional media employed by teachers. This study aimed to examine the effects of learning motivation and offline educational games on social studies learning outcomes among fourth-grade students. A quantitative approach using an ex post facto design was employed. The subjects were 28 fourth-grade students at one public elementary school (SDN) in Danau Kerinci District, Kerinci Regency, selected through total sampling. Data were collected through five-point Likert-scale questionnaires and official academic score documentation, then analyzed using multiple linear regression, the coefficient of determination, the t-test, and the F-test. Prior to the main analysis, classical assumption tests were conducted, including normality, linearity, multicollinearity, and heteroscedasticity tests, all of which were satisfied. The results revealed that learning motivation had a significant positive partial effect on social studies learning outcomes (t = 4.82, p < .05), as did offline educational games (t = 3.61, p < .05). The F-test confirmed a significant simultaneous effect of both variables (F = 18.47, p < .05), with a coefficient of determination of R² = 0.61, indicating that both variables jointly explained approximately 61% of the variance in learning outcomes. These findings suggest that integrating motivational strategies with offline educational game media can meaningfully enhance student achievement in social studies, particularly in rural primary schools with limited digital infrastructure.